2017
DOI: 10.1371/journal.pone.0182544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lay support for pregnant women with social risk factors on infant development and maternal psychological health at 12 months postpartum

Abstract: BackgroundThe ELSIPS (Evaluation of Lay Support in Pregnant Women with Social Risk) RCT showed that lay support for women with social risk had a positive effect on maternal mental health and mother-infant bonding. This exploratory study examined whether these observed benefits would impact infant development at 1 year.MethodsA sub-sample of women whose infants were under one year who had participated in the ELSIPS RCT which randomised women to receive either standard care or the services of a Pregnancy Outreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Two studies have found that lack of social support predicted maternal depressive symptoms among immigrant Arab American mothers (Alhasanat, 2017;Alhasanat-Khalil et al, 2018). Infants whose mothers had higher levels of social support had better cognitive and language development at 12 months of age (Popo et al, 2017).Therefore, social support in immigrant families may be a key variable to examine as it might affect their stress and depressive symptoms as well as infant outcomes. Social support may also be a factor for which interventions could be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have found that lack of social support predicted maternal depressive symptoms among immigrant Arab American mothers (Alhasanat, 2017;Alhasanat-Khalil et al, 2018). Infants whose mothers had higher levels of social support had better cognitive and language development at 12 months of age (Popo et al, 2017).Therefore, social support in immigrant families may be a key variable to examine as it might affect their stress and depressive symptoms as well as infant outcomes. Social support may also be a factor for which interventions could be developed.…”
Section: Introductionmentioning
confidence: 99%
“…At fourteen months, depressive symptoms in the third trimester of pregnancy were associated with delay in the gross motor area. Morais et al (2013) and Popo et al (2017) also identified symptoms of maternal depression as indicators of delay in gross motor development at 12 months of age. According to Koutra et al (2013) the consequences of gestational and postnatal depression are diverse for the different subareas of development.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding development, studies focused on impairments for the child's initial development (Gerstein et al, 2017;Popo, Kenyon, Dann, MacArthur, & Blissett, 2017). With older subjects, age ranging from 5 to 12, maternal depression was a risk factor for social development (Villaseñor, Calderón Hernández, Gaytán, Romero, & Díaz-Barriga, 2017).…”
mentioning
confidence: 99%
“…Interventions assessed for sustainability 1 to 7 years later (n = 5 studies) revealed that former impacts on anthropometric outcomes at intervention conclusion (if any) were not maintained, nor improved, at the next follow-ups. 58,65,69,76,84 Better sustainability was however observed for feedings practices and EBRBs. 58,65 Although not in the scope of the current review, it is noteworthy that some of the broad parent support programs had a positive impact on various aspects of childbirth preparation (e.g., epidural/pain medication during labor), 86,87 the mother-to-infant bonding, 75,76 safety of new-born care practices, 86,87,89 the child health and development (e.g.…”
Section: Impact On Outcomesmentioning
confidence: 97%